The factor influencing self-sensing property of carbon fiber. (16th June 2023) - Shin, Pyeong-Su; Baek, Yeong-Min; Kim, Jong-Hyun; Kwon, Dong-Jun
Abstract: In previous many publications, the self-sensing of carbon fiber reinforced plastic (CFRP) had been researched using change in electrical resistance (CER) by the external load. To improve the analysis accuracy of self-sensing results, the CER analysis should be studied more clearly in micro scale. In this paper, we tried to analyze CER of CFRP in three-point bending test compared with dual fiber composite (DFC). In DFC specimen, the CER trend of dual CF, which was embedded to different position, could be determined. In the case of CF, which was embedded on the upper side, the initial CER of CF decreased by compressive load. However, the CER was finally increased due to the fracture. In the case of below side, however, the CER of CF increased by tensile load as the time increased. The CER behavior of CFRP was similar with DFC while the CER of CFRP was changed more largely than the DFC case by contacted interface between two fractured CFs. Ultimately, the CER trend of CFRP could be predicted using DFC, which was micro scale, and the self-sensing of CFRP was affected by the interface between CFs in composite materials. Graphical abstract: Image 1